Summation of Fourier-Laplace Series in the Space L(S^m) - Lasuriya, R. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We establish estimates of the rate of convergence of a group of deviations on a sphere in the space L(S^m),m > 3.